Southern Ocean Precipitation Characteristics Observed From CloudSat and Ground Instrumentation During the Macquarie Island Cloud & Radiation Experiment (MICRE): April 2016 to March 2017. Issue 5 (8th March 2022) - Tansey, Emily; Marchand, Roger; Protat, Alain; Alexander, Simon P.; Ding, Saisai
Abstract: A 1‐year blended surface precipitation data set using Parsivel disdrometer, surface W‐band radar, and tipping bucket measurements is produced for the Macquarie Island Cloud and Radiation Experiment (MICRE) and compared with retrievals from CloudSat (spaceborne 94 GHz radar). Surface precipitation was observed 44% ± 4% of the time between April 2016 and March 2017. Precipitation composed primarily of small particles (diameter <1 mm) occurred about 36% ± 2% of the time, constituting 10% of total accumulation. Remaining precipitation contained enough large particles such that the disdrometer could be used to identify the precipitation type as rain, ice, snow or wet snow. Seasonal and annual statistics on frequency of occurrence and accumulation for each precipitation type observed during MICRE are presented. Most ice and mixed phase precipitation was shallow, originating at a height of 3 km or lower, and occurred most often when Macquarie Island was to the northwest of the nearest cyclonic low‐pressure center. In contrast, rain was more often deep and occurred most frequently when the island was to the southeast of cyclonic lows. A weak diurnal cycle in frequency and mean rate was present with a minimum between 12:00 and 14:00 local time and maximum between 03:00 and 06:00 local time. The CloudSat 2C‐Precip‐Column product missed the lightest precipitation (because the near‐surface reflectivity is <−15 dBZ) and overestimated total liquid precipitation and occurrence of mixed phase precipitation, but captured reasonably well the distribution of rain rates for rates >0.5 mm/hr. Plain Language Summary: Understanding the nature of precipitation over the Southern Ocean (SO) is crucial to understanding cloud properties, which climate models struggle to simulate correctly with significant impacts on global climate sensitivity (how much the Earth is likely to warm due to increases in greenhouse gases). Studies assessing the performance of climate simulations rely primarily on satellite measurements and reanalysis of precipitation in remote regions like the SO due to the lack of available surface measurements. However, there are large disagreements between and among satellite and reanalysis products regarding SO precipitation characteristics. This study examines precipitation characteristics obtained from a recent field campaign located at Macquarie Island, in the middle of the SO. The analysis presented here focuses on SO precipitation type (liquid, frozen or mixed) and accumulation, as well as seasonal and storm‐related variability. Ground observations from Macquarie Island are also compared to CloudSat satellite precipitation estimates that are a crucial data source for precipitation in the region. Key Points: Macquarie Island Cloud and Radiation Experiment data are used to study seasonal, diurnal, and synoptic variation in surface precipitation Rain, ice/mixed, and small particle precipitation occurred year‐round, comprising 74%, 16%, and 10% of total accumulation, respectively CloudSat 2C‐Precip‐Column overestimated liquid accumulation and mixed phase occurrence but underestimated light precipitation occurrence